2018
DOI: 10.1017/s0020859018000317
|View full text |Cite
|
Sign up to set email alerts
|

The Land–Labour Hypothesis in a Settler Economy: Wealth, Labour and Household Composition on the South African Frontier

Abstract: Traditional frontier literature identifies a positive correlation between land availability and fertility. A common explanation is that the demand for child labour is higher in newly established frontier regions compared to older, more densely populated farming regions. In this paper, we contribute to the debate by analysing the relationship between household composition and land availability in a closing frontier region, i.e. the Graaff-Reinet district in South Africa’s Cape Colony from 1798–1828. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…They [15] studied the blockchain network via measurement and analysis from a specific view. They [4], [16] studied the Hyperledger fabric and found that the throughput grows almost linearly with the transaction arrival rate until reaching the systems peaking processing rate.…”
Section: Resultsmentioning
confidence: 99%
“…They [15] studied the blockchain network via measurement and analysis from a specific view. They [4], [16] studied the Hyperledger fabric and found that the throughput grows almost linearly with the transaction arrival rate until reaching the systems peaking processing rate.…”
Section: Resultsmentioning
confidence: 99%
“…The Malthusian Trap. We found an interesting phenomenon that mining pools are caught in a Malthusian trap [35], [36], where an exponential growth of the hash rate does not mean an increasing hash rate proportion of a mining pool. On the converse, some mining pools' hash rate proportions are actually decreasing despite an exponential growth of the hash rate.…”
Section: Hash Rate Distributionmentioning
confidence: 88%
“…Land was, of course, as important as labour for this pre-industrial society. Analysing the relationship between household composition and land availability in the Graaff-Reinet district from 1800 to 1828, Cilliers and Green (2017) show that the number of children present in farming households increased with frontier closure, while the presence of non-family labourers decreased over time. The demand for family labour, they argue, was not a function of its marginal productivity.…”
Section: European Settlementmentioning
confidence: 99%